A New Index of Uncertainty Based on Internet Searches: A Friend or Foe of Other Indicators? - Maria Elena Bontempi; Roberto Golinelli; Matteo Squadrani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
The preliminary evidence in the literature suggests that changes in uncertainty have a role in shaping the U.S. economic cycle. But what is effectively measured by the different available indicators of uncertainty still remains an "uncertain" issue. This paper has two aims: (i) to introduce a new uncertainty indicator (GT) based on Internet searches; and (ii) to compare the main features and the macroeconomic effects of alternative measures of uncertainty, including our own. Results suggest that GT shocks embody timely information about people's perception of uncertainty and, in some cases, earlier than other indexes. Furthermore, the effect of uncertainty shocks on output is more influenced by parameter breaks due to insample events than by model specification. The consequence is that an all-comprehensive indicator able to weight different sources of uncertainty is preferable.
Keywords: D80; E32; E27; E37; C32; 330